Punctuation as a window to syntactic awareness - Costa, Ana Luísa (2022)
More than developing a study on punctuation, this paper intends to explore the uses of punctuation as a window to syntactic awareness or metasyntactic abilities. Different theoretical models identify several degrees of conscious access to linguistic knowledge and types of metalinguistic verbalizations. The analysis of canonical and deviant punctuation in adult academic writing contributes to the characterization of different degrees of syntactic awareness, corroborating some theoretical hypotheses under discussion in section 2. A case study is the methodological approach adopted to study undergraduate students’ punctuation. The analysis included four tasks: (i) written production, (ii) error correction task, (iii) metalinguistic explanation, and (iv) verbalized conceptions in a focus group. Results, presented in section 4, show a general dissociation between explicit knowledge of the punctuation rules and general success in its uses. Conclusions point to some clues for an academic writing pedagogy and a more complex concept of “syntactic awareness”, in which different degrees of controlled access and verbalization abilities must be considered.